2015
DOI: 10.1007/s00521-015-2092-8
|View full text |Cite
|
Sign up to set email alerts
|

ICA-based speed control of induction motor fed by wind turbine

Abstract: This paper proposes the speed control of induction motor fed by wind turbine using Imperialist Competitive Algorithm (ICA). The wind turbine plays as a prime mover to a connected DC generator. Pulse-width modulation is used to get three-phase AC voltage from the output of DC generator. The proposed design problem of speed controller is established as an optimization problem. ICA is adopted to search for optimal controller parameters by minimizing the time domain objective function. The behavior of the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…en the remote controller executes the motor control instructions according to the control signal sent by the master controller and returns the sensor measurement data to the master controller [21,22]. In the process of permanent magnet synchronous motor servo control, it is found that the motor speed is greatly affected by the current.…”
Section: Modeling Of Networked Control Structure System Of Induction ...mentioning
confidence: 99%
“…en the remote controller executes the motor control instructions according to the control signal sent by the master controller and returns the sensor measurement data to the master controller [21,22]. In the process of permanent magnet synchronous motor servo control, it is found that the motor speed is greatly affected by the current.…”
Section: Modeling Of Networked Control Structure System Of Induction ...mentioning
confidence: 99%
“…The study of a wind energy conversion system (WECS) based on Permanent Magnet Synchronous Generator by using an appropriate control is considered in many papers described [22][23][24][25][26][27]. Most previous systems have proposed testing the system via step variations of normal or high induction motor rotor speed only [28,29]. To evaluate the system performance with the proposed controller, variations of low IM rotor speed test should be applied [30,31].…”
Section: Of 17mentioning
confidence: 99%
“…Although data‐driven models are more accurate without the need to specify a precise functional form, the complexity of computation and time consuming limit their practical application values [19]. The fault detection of WTs should be timely and rapid, providing sufficient time for the maintenance of operators to deal with various abnormal conditions.…”
Section: Introductionmentioning
confidence: 99%